2021
DOI: 10.3390/ijms22052366
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Evaluation in Ischemia Reperfusion Models: Characteristics, Limits and Perspectives

Abstract: Ischemia reperfusion injury is a complex process consisting of a seemingly chaotic but actually organized and compartmentalized shutdown of cell function, of which oxidative stress is a key component. Studying oxidative stress, which results in an imbalance between reactive oxygen species (ROS) production and antioxidant defense activity, is a multi-faceted issue, particularly considering the double function of ROS, assuming roles as physiological intracellular signals and as mediators of cellular component da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 118 publications
0
16
0
Order By: Relevance
“…Reperfusion induces tissue reactions that fuel the production of ROS, sequestration of proinflammatory immunocytes in ischemic tissues, endoplasmic reticulum stress, and the development of postischemic capillary "no-reflow", which exacerbate tissue damage. Thus, OS is one of the most important pathological mechanisms of reperfusion injury, which causes apoptosis, autophagy, inflammation, and other tissue damage in several ways, ultimately causing irreversible damage to organs [8][9][10]. Ischemic/reperfusion injury is the most common cause of disease and death, and is a widespread problem in organ transplantation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Reperfusion induces tissue reactions that fuel the production of ROS, sequestration of proinflammatory immunocytes in ischemic tissues, endoplasmic reticulum stress, and the development of postischemic capillary "no-reflow", which exacerbate tissue damage. Thus, OS is one of the most important pathological mechanisms of reperfusion injury, which causes apoptosis, autophagy, inflammation, and other tissue damage in several ways, ultimately causing irreversible damage to organs [8][9][10]. Ischemic/reperfusion injury is the most common cause of disease and death, and is a widespread problem in organ transplantation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested that oxidative stress could be regulated by multiple molecular mechanisms [18][19][20]. Oxygen supply to renal IRI leads to the formation of ROS and inflammatory response, and the overproduction of ROS is considered possible causes of renal IRI [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…TIA has no infarcts, while RIND, stroke in evolution, and completed stroke have varying cerebral infarcts. Neurons lose their ability to maintain normal transmembrane ionic gradients after ischemia [ 50 ] and then cause a series of pathological changes, such as oxidative stress [ 51 ], excitotoxicity, inflammation [ 52 ], and apoptosis [ 53 ]. Increased ROS triggers oxidative stress after ischemia-reperfusion and then aggravates blood-brain barrier injury.…”
Section: Pathophysiological Mechanisms Of Ischemic Strokementioning
confidence: 99%